Doing visual research - Mitchell, Claudia (Sage Publications Ltd, 2011)
This work offers an introduction to the use of photography, collaborative video, drawing, objects, multi-media production and installation in research. The author explains how visual methods can be used as modes of inquiry as well as modes of representation for social research. The book looks at a range of conceptual and practical approaches to a range of tools and methods, while also highlighting the interpretive and ethical issues that arise when engaging in visual research. She draws on her own work in the field of visual research throughout to offer extensive examples from a variety of settings and with a variety of populations. Topics covered include: Photographs and memory work studies; Drawing as a participatory visual methodology; Working with images, Writing about images; Can visual methods make a difference? : from practice to policy. This book takes an interdisciplinary approach to the subject of visual research, producing a practical introduction to the subject.